Spatial crop yield estimation based on remotely sensed stress index - Holzman, Mauro (2014)
The improvement of methods to evaluate the real impact of soil moisture availability on crop systems is crucial because the importance for world economy and food production. The relationship between the remote sensed stress index TVDI, root-zone soil moisture and soybean yield was analyzed in a sandy region of Argentine Pampas. High correlation (R2 =0.68) between TVDI and soybean yield was observed. The obtained adjustment allows us to evaluate the spatial variability of yield during a humid and dry period 2-3 months before harvest. Since the method requires remote sensed data, it could be applied over areas with poor data coverage.